How Pharaohs Became Media Stars Ancient Egypt and Popular Culture - Fernandez Pichel, Abraham I. (2024)
The appearance of new media and its enormous diffusion in the last decades of the 20th century and up to the present has greatly increased and diversified the reception of Egyptian themes and motifs and Egyptian influence in various cultural spheres. So-called 'popular' or 'pop' culture (cinema, genre fiction, TV-series, comics, graffiti, computer and video games, rock and heavy music, radio serials, among others) often makes use of narratives and motifs drawn from the observation and study of ancient Egypt, updated and reinterpreted in various ways, and which is now the subject of study by scholars of Egyptology. The present monograph seeks to provide new evidence of this interdisciplinarity between Egyptology and popular culture. It explores the conscious reinterpretation of the past in the work of contemporary authors, who shape an image of the Egyptian reality that in each case is determined by their own circumstances and contexts.